Noise Abatement Approach Using Computer Simulation Model for Urban Indian Road of a Tier-2 City - SONAVIYA, Dipeshkumar Ratilal; TANDEL, Bhaven N (Archives of Acoustics, 2021)
Noise pollution is a major problem nowadays. In urban context, road traffic is the main source of noise pollution. People directly exposed to road traffic noise suffer from moderate to severe annoyance, headache, stress, feeling of exhaustion, and reduced work performance efficiency. As the sources and severity of noise pollution continue to grow, new approaches are needed to reduce the exposure. In this research, noise abatement has been investigated using a computer simulation model (SoundPLAN essential 4.0). Noise maps were developed using SoundPLAN essential 4.0 software. Noise maps are very beneficial to identify the impact of noise pollution. Data required for mapping are noise data (LAeq), road inventory data, geometric features of mapping area, category wise traffic counts, category wise vehicle speed, meteorological data such as wind velocity, humidity, temperature, air pressure. LAeq observed on all locations of the Central zone of Surat city was greater than the prescribed central pollution control board (CPCB) limits during day time and night time. This paper is focused on using acoustic software for the simulation and calculation methods of controlling the traffic noise. According to the characteristics of traffic noise and the techniques of noise reduction, road traffic noise maps were developed using SoundPLAN essential 4.0 software to predict the scope of road traffic noise. On this basis, four reasonable noise control schemes were used to control noise, and the feasibility and application effect of these control schemes can be verified by using the method of simulation modelling. The simulation results show that LAeq is reduced by up to 5 dB(A). The excess noise can be efficiently reduced by using the corresponding noise reduction methods.